The Utilization of Geospatial Technologies in Urban Vegetation Ecosystems Conservation: A Review - Tolulope Ayodeji Olatoye*; Sonwabo Perez Mazinyo; Ahmed Mukalazi Kalumba (Journal of Studies in Social Sciences and Humanities, 2023)
This research is focused on a review of geospatial technologies (such as Remote Sensing and Geographic Information Systems technologies) in monitoring vegetation land use land cover (LULC) conservation. This study is considered very apt and timely because of the ecological challenges and intricacies associated with the paradoxical phenomenon chracterized by conflicting land use practices of urban development as well as the conservation of vegetation LULC in many parts of the world today. It is also imperative to note that the literature reviewed for this research is rich, diversified and developed based on relevant themes in the specific field of study. Relevant literature on the applications of geo-information technologies, and the conservation of vegetation were specifically sourced from internationally recognized academic publications, electronic data sources and other educational websites. This study makes a clarion call towards the conservation of degraded vegetation environments and proffers solutions towards the actualization of environmental sustainability of these fragile ecosystems.